Dietary supplementation of active dry yeast (Saccharomyces cerevisiae) to finishing bulls: effects on growth performance, blood hormones, fatty acid concentrations in the gastrointestinal tract and trace mineral elements utilisation - Jiaming Luan; Xin Feng; Dongxu Yang; Meng Yang; Yinghai Jin; Min Zhang; Chunyin Geng (Italian Journal of Animal Science)
This study was conducted to investigate the effects of dietary supplementation of active dry yeast (Saccharomyces cerevisiae) on growth performance, circulating ghrelin, fatty acid concentrations in the gastrointestinal tract, and trace mineral elements utilisation of finishing bulls. Twenty Yanbian cattle (bulls) [body weight (BW) 485 ± 38 kg] were randomly divided into two groups (control and treatment groups) and participated in a 100-day finishing trial. The control group (CON) was fed a basal diet (total mixed ration, TMR). The treatment group (active dry yeast, ADY) was fed a basal diet supplemented with ADY (Levucell SC, Saccharomyces cerevisiae CNCM I-1077, viable count ≥8.0 × 109 CFU/g, 1.0 g/bull/day). ADY supplementation significantly increased the dry matter intake (DMI) of bulls (p < .05); significantly increased the concentration of ghrelin O-acyl transferase (GOAT) (p < .05), significantly decreased the concentration of corticotropin-releasing hormone (CRH) (p < .05), tended to increase the concentration of acyl ghrelin (AG) (p = .053) in serum; significantly increased the content of C12:0 in duodenal digesta, the apparent digestibility of Zn, the concentrations Zn and Cu in serum and the deposition of Cu in the liver (p < .05), significantly decreased the deposition of Fe in muscle in finishing bulls (p < .05). In conclusion, ADY supplementation improved DMI of finishing bulls may be related to the change of AG, and a potential mechanism for the change of AG by ADY supplementation is via its effects on the metabolism of C12:0, Zn, and Cu in finishing bulls.HIGHLIGHTS Active dry yeast (ADY) supplementation increased the dry matter intake (DMI) and tended to increase the concentration of acyl ghrelin (AG) in the serum of finishing bulls. ADY supplementation increased the content of C12:0 in duodenal digesta and improved the bioavailability of Zn and Cu of finishing bulls. A potential mechanism for the change of AG by ADY supplementation is via its effects on the metabolism of C12:0, Zn, and Cu in finishing bulls.